Please solve for x. ln(x+2) - ln(3x + 1) = 4

Expert Answers

An illustration of the letter 'A' in a speech bubbles

ln (x+2) - ln (3x+1) = 4

We know that ln a - ln b = ln a/b

==> ln (x+2)/(3x+1) = 4

==> (x+2)/(3x+1) = e^4

==> x+2 = (3x+1)*e^4

==> x+2 = 3(e^4)x + 3^4

==> 3(e^4)x - x = e^4 - 2

==> x(3e^4 - 1) = e^4 - 2

==> x = (e^4 - 2)/(3e^4 - 1)  

 

Approved by eNotes Editorial Team
Soaring plane image

We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

  • 30,000+ book summaries
  • 20% study tools discount
  • Ad-free content
  • PDF downloads
  • 300,000+ answers
  • 5-star customer support
Start your 48-Hour Free Trial